Bimbingan Agama Islam bagi Komunitas Muallaf di Bokor Kabupaten Bangka: Islamic Guidance for the Convert Community in Bokor, Bangka Regency - Musa, Musa; Zakirman, Al Fakhri; Marsudi, Muhammad Sholeh; Firdaus, Wahyu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
One of the most crucial issues faced by converts is the matter of religious guidance. Being adults, the stigma associated with some individuals impedes converts from learning about Islam more profoundly. This activity helps address the challenges encountered by converts by making them more comfortable learning about their religion. The learning takes place within their community, where the level of religiosity is similar. The activity employs the Participatory Rural Appraisal (PRA) method, emphasizing participant involvement. The implementation of this activity aligns with the planned objectives and proceeds smoothly, being readily accepted by converts.